Varieties of Anomalous Experience: Examining the Scientific Evidence (2nd Ed.). 2014
DOI: 10.1037/14258-011
|View full text |Cite
|
Sign up to set email alerts
|

Past-life experiences.

Abstract: Ajendra Singh Chauhan (Mills, 2004), a boy in northern India, repeatedly described memories of a past life when he was between 36 and 60 months old. His case was first identified by G. S. Gaur, who recorded Ajendra's statements as described by his father in 1992, when Ajendra was 13 years old. According to his father, when Ajendra was about 3 years old, he was offered a glass of milk at his aunt's home and remarked, "I used to have a mare. Two water buffaloes used to give milk. I used to drink a bucket of milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…With a few exceptions, demographic factors including age, gender, socioeconomic status (SES), and ethnicity, as well as intelligence and education, do not generally differentiate those likely to exhibit AEs. With respect to age, spontaneous reports of past lives typically occur between 2 to 6 years of age (Mills & Tucker, 2014), whereas mystical experiences are more likely to manifest at middle age or later (Wulff, 2014; see also Granqvist, Reijman, & Cardeña [2011] for a general consideration of developmental aspect in alterations of consciousness). Overall, more women than men report psi-related experiences and spirit possession and similar phenomena (Cardeña & Alvarado, 2014; Watt & Tierney, 2014), although for the latter cultural changes such as greater acceptance of gays and transgender people has started to blur this distinction (Schaffler, Cardeña, Reijman, & Haluza, 2016).…”
Section: Aes Individual Differences and Personality Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…With a few exceptions, demographic factors including age, gender, socioeconomic status (SES), and ethnicity, as well as intelligence and education, do not generally differentiate those likely to exhibit AEs. With respect to age, spontaneous reports of past lives typically occur between 2 to 6 years of age (Mills & Tucker, 2014), whereas mystical experiences are more likely to manifest at middle age or later (Wulff, 2014; see also Granqvist, Reijman, & Cardeña [2011] for a general consideration of developmental aspect in alterations of consciousness). Overall, more women than men report psi-related experiences and spirit possession and similar phenomena (Cardeña & Alvarado, 2014; Watt & Tierney, 2014), although for the latter cultural changes such as greater acceptance of gays and transgender people has started to blur this distinction (Schaffler, Cardeña, Reijman, & Haluza, 2016).…”
Section: Aes Individual Differences and Personality Traitsmentioning
confidence: 99%
“…With regard to changes perhaps attributable to available information, Athappilly, Greyson, and Stevenson (2006) found that a comparison of reports before and after NDEs became widely known showed very few differences. In contrast, ostensible past lives as animals are more frequently reported in cultures in which animals are held in high esteem (Mills & Tucker, 2014).…”
Section: Anomalous Experiences and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Further, if we consider an overinclusive cognitive style as a predictor of both psychopathology and enhanced creativity (Carson, 2011), belief in and experience of past lives may be a protective factor that promotes creative rather than psychopathological outcomes. Rather than constituting an area of investigation fraught with stigma and even derision, as Mills and Tucker (2014) have observed, the study of PLM may produce valuable information about creative minds.…”
Section: Discussionmentioning
confidence: 96%
“…First, we predicted that subjects in the high (vs. low) creative achievement group would be more likely to report actual memories of past lives. However, the prevalence of PLM in the general population is very low (Mills & Tucker, 2014); accordingly, we expected few subjects with PLM, but we suspected that past life beliefs (PLB) would not be as uncommon. Second, we also predicted that subjects in the high (vs. low) creative achievement group would be more likely to report PLB.…”
Section: Study Twomentioning
confidence: 96%